Quantifying hitting load in racket sports: A scoping review of key technologies - Brich, Q.; Casals, M.; Crespo, M.; Reid, M.; Baiget, E. (International Journal of Sports Physiology and Performance, 2024)
Purpose This scoping review aims to identify the primary racket and arm-mounted technologies based on inertial measurement units that enable the quantification of hitting load in racket sports.